Economic empowerment based on the strengthening of social capital in the implementation of village-owned enterprises - Leylia Khairani; Ramlan Ramlan; Delyana Rahmawany Pulungan (Masyarakat, Kebudayaan dan Politik, 2021)
Village-owned enterprises or Badan Usaha Milik Desa (BUMDes) is currently trying to realize Indonesia’s development from the periphery by strengthening villages' unitary framework state. However, BUMDes in North Sumatera have not utilized the potential of natural resources and the village’s potential. This study aims to reveal forms of economic empowerment based on strengthening social capital in implementing BUMDes. This study uses qualitative method research and the data were obtained through in-depth interviews to determine citizens’ involvement and participation in developing of BUMDes. This study found that community economic empowerment through the implementation of BUMDes in Mandailing Natal Districts reveals several elements of the role of social capital, which includes; 1) The involvement and participation of the community which is quite large. 2) Relationships between BUMDes managers, village leaders, and community members in the implementation of BUMDes are built based on the social system and cultural values of the Mandailing community. 3) Social norms and community beliefs refer to the social system and cultural values of the Mandailing community. Social capital that has been built through the social and cultural system strengthens trust in village-owned enterprises governance as an effort to empower the community’s economy in Mandailing Natal.